Process for the production of betacyanin pigments. - Abd Manap, Mohd Yazid; Mohd Ghazali, Hasanah; Naderi, Nassim (2008)
The present invention provides a process for the production of betacyanin pigments which comprises reacting pulp derived from a plat which belongs to Hylocereus polyrhizus and which can produce betacyanin pigments, in a solvent extraction system.